2024
DOI: 10.1002/solr.202300994
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalenediimide‐Based Polymer Dots with Dual Acceptors as a New Class of Photocatalysts for Photocatalytic Hydrogen Generation under Visible Light Irradiation

Islam M. A. Mekhemer,
Ying‐Sheng Wu,
Ahmed M. Elewa
et al.

Abstract: Organic conjugated polymer dots (Pdots) are emerging as promising photocatalysts for solar‐driven hydrogen production. However, organic solvents are commonly used as cosolvents in photocatalytic systems to promote the dispersion of organic materials and improve the overall efficiency of the photocatalytic process. Herein, two naphthalenediimide (NDI)‐based Pdots, with and without surfactant, are fabricated and presented as highly efficient and stable photocatalysts for visible‐light‐driven hydrogen generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…All the commercially available reagents were purchased from Signa-Aldrich unless otherwise noted. The monomers including 2,7-bis­(8-(methyldioctylsilyl)­octyl)-4,9-bis­(tributylstannyl)­benzo­[lmn]­[3,8]­phenanthroline-1,3,6,8­(2H, 7H)-tetraone ( NDI ), 4,7-bis­(5-bromoselenophen-2-yl)-5,6-difluorobenzo­[c]­[1,2,5]­thiadiazole ( S ), and 4,7-bis­(5-bromo-selenophen-2-yl)-2-(2-ethylhexyl)-5,6-difluoro-2H-benzo­[d]­[1,2,3]­triazole ( N ) are synthesized based on the reported literature . The detailed synthesis of 2,7-bis­(8-(methyldioctylsilyl)­octyl)-4,9-bis­((E)-2-(tributylstannyl) vinyl)­benzo­[lmn]­[3,8]­phenanthroline-1,3,6,8­(2H,7H)-tetraone ( v-NDI ) is described in the Supporting Information, and the process is based on methods reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All the commercially available reagents were purchased from Signa-Aldrich unless otherwise noted. The monomers including 2,7-bis­(8-(methyldioctylsilyl)­octyl)-4,9-bis­(tributylstannyl)­benzo­[lmn]­[3,8]­phenanthroline-1,3,6,8­(2H, 7H)-tetraone ( NDI ), 4,7-bis­(5-bromoselenophen-2-yl)-5,6-difluorobenzo­[c]­[1,2,5]­thiadiazole ( S ), and 4,7-bis­(5-bromo-selenophen-2-yl)-2-(2-ethylhexyl)-5,6-difluoro-2H-benzo­[d]­[1,2,3]­triazole ( N ) are synthesized based on the reported literature . The detailed synthesis of 2,7-bis­(8-(methyldioctylsilyl)­octyl)-4,9-bis­((E)-2-(tributylstannyl) vinyl)­benzo­[lmn]­[3,8]­phenanthroline-1,3,6,8­(2H,7H)-tetraone ( v-NDI ) is described in the Supporting Information, and the process is based on methods reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…NDI-S/N was prepared according to methods reported in the literature . The monomers v-NDI, S / N , and the catalyst Pd­(PPh 3 ) 4 (5 mol % relative to v-NDI ) were added into a microwave vessel containing chlorobenzene (0.1 M).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Recently, our group reported that the incorporation of a donor into dual acceptor systems (D–A–A) offers a promising approach for overcoming the limitations of traditional photocatalysts in H 2 evolution. 27,28 Consequently, the D–A–A system, which results in the push–pull–pull approach able to enhance light absorption, suppress charge recombination, tune redox potentials, improve stability, and integrate with other systems, makes them a valuable tool for the development of efficient and sustainable solar-driven H 2 production technologies, while it is still rarely explored for COFs thus far. In this context, the incorporation of imide and imine moieties into 2D COFs was constructed for the first time while converting 1D ribbons into 2D COFs but without a further study of the catalytic applications.…”
Section: Introductionmentioning
confidence: 99%